1978
DOI: 10.1001/archpedi.1978.02120260057014
|View full text |Cite
|
Sign up to set email alerts
|

The Hemolytic-Uremic Syndrome

Abstract: A review of our experience with the hemolytic-uremic syndrome (HUS) illustrates a broad spectrum of severity. Comparison of this experience with that in other parts of the world leads to the following conclusions: (1) Nondiarrheal HUS may be sufficiently different from postdiarrheal HUS to warrant separate consideration in clinical studies. (2) The Netherlands more closely resembles California than Argentina in having patients with less severe acute renal disease and a more favorable outcome. (3) In California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

1979
1979
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…A systematic review of published case series identified 5999 children with sporadic diarrhoea‐associated HUS in 38 articles (reporting 39 case series) from 14 countries (Table III) (Dolislager & Tune, 1978; Raghupathy et al , 1978; Fong & Kaplan, 1982; Karmali et al , 1983, 1985; Communicable Disease Surveillance Centre, 1986; Rogers et al , 1986; Sheth et al , 1986; Badami et al , 1987; Kinney et al , 1988; Novillo et al , 1988; Lopez et al , 1989; Tarr et al , 1989; Martin et al , 1990; Milford et al , 1990; Abu‐Arafeh et al , 1991; Rowe et al , 1991, 1993; Bitzan et al , 1993; Gianviti et al , 1994; Jernigan & Waldo, 1994; Van de Kar et al , 1995, 1996; Douglas & Kurien, 1997; Nevard et al , 1997; Siegler et al , 1997; Rowe et al , 1998; Oakes et al , 2006; Decludt et al , 2000; Wong et al , 2000; Elliott et al , 2001; Chandler et al , 2002; Cummings et al , 2002; Gerber et al , 2002; Trachtman et al , 2003; Lynn et al , 2005; Haus‐Cheymol et al , 2006; Bergstein et al , 1992). Among the 2880 children in whom diarrhoea was described as either bloody or not bloody, 1890 (66%) had bloody diarrhoea.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of published case series identified 5999 children with sporadic diarrhoea‐associated HUS in 38 articles (reporting 39 case series) from 14 countries (Table III) (Dolislager & Tune, 1978; Raghupathy et al , 1978; Fong & Kaplan, 1982; Karmali et al , 1983, 1985; Communicable Disease Surveillance Centre, 1986; Rogers et al , 1986; Sheth et al , 1986; Badami et al , 1987; Kinney et al , 1988; Novillo et al , 1988; Lopez et al , 1989; Tarr et al , 1989; Martin et al , 1990; Milford et al , 1990; Abu‐Arafeh et al , 1991; Rowe et al , 1991, 1993; Bitzan et al , 1993; Gianviti et al , 1994; Jernigan & Waldo, 1994; Van de Kar et al , 1995, 1996; Douglas & Kurien, 1997; Nevard et al , 1997; Siegler et al , 1997; Rowe et al , 1998; Oakes et al , 2006; Decludt et al , 2000; Wong et al , 2000; Elliott et al , 2001; Chandler et al , 2002; Cummings et al , 2002; Gerber et al , 2002; Trachtman et al , 2003; Lynn et al , 2005; Haus‐Cheymol et al , 2006; Bergstein et al , 1992). Among the 2880 children in whom diarrhoea was described as either bloody or not bloody, 1890 (66%) had bloody diarrhoea.…”
Section: Resultsmentioning
confidence: 99%
“…In deed, many investigators feel that there are multiple causes [1,4,5,10]. In children, enteric viral infections frequently precede the onset of the disease and there is evi dence of an association with mumps and certain Coxsackie viruses [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…Dem eigentlichen Krankheitsbild geht ein Prodromalstadium voraus, das sich normalerweise in einer Infektion des Darmtraktes äußert. Krampfartige Bauchbeschwerden, Meteorismus, blutiges Erbrechen, blutige schleimige Stühle und gelegentlich massiver Aszites können einen Ileus oder eine Peritonitis vortäuschen (2,5,6,14,17). Diese Krankheitserscheinungen werden allerdings nicht nur im prodromalen, sondern auch im Stadium der Anurie beobachtet.…”
Section: Einführungunclassified
“…Trotz herrsc he nder Ansicht, daß Darmerscheinu nge n beim H U S ei nen milden Verl a u f nehmen (2,17), können Veränderungen im Ber eich des Da rm tra ktes oftma ls Ursache n sowo hl d iag nos tisc her als auch t hera pe utischer Feh ler sein und damit eine n prognost isch en Einfluß ha ben (7, 11, 12,13 ,15).…”
Section: Diskussionunclassified